Análisis de sensibilidad y resistencia antimicrobiana en patógenos de infecciones urinarias en pacientes con diabetes mellitus tipo II, Machala 2024 - Cuenca Ajila, Anthony Paul; Llivigañay Villao, Mayra Alexandra (My University, 2024)
Introduction: Urinary tract infections (UTI), in diabetic patients can cause serious complications such as bacteremia. The main associated risk factors are: polyuria, cystitis, dysuria and pyelonephritis, conditions that contribute to a higher incidence in this population. The aim of this study was to determine the most frequent bacteria in patients with Type II Diabetes Mellitus (DM II) who presented UTI, through the analysis of clinical histories and a database for the measurement of microbial sensitivity and resistance. A descriptive and cross-sectional study was carried out, reviewing clinical histories and databases with DM II patients who attended a private laboratory. The information collected included microbiological data related to UTI. The data obtained were processed and analyzed statistically, using percentages to describe the distribution of microorganisms, sensitivity profiles and antimicrobial resistance. Results: The microorganisms identified were Escherichia coli, the most frequent pathogen, representing 37.5% of the isolates, followed by Staphylococcus aureus (23.75%), Streptococcus agalactiae (17.5%) and members of the Enterobacteriaceae family (10%). Regarding antimicrobial resistance, gentamicin showed higher levels of resistance, reaching 89.33%. On the other hand, the antibiotics with the highest frequency of sensitivity were amikacin, ciprofloxacin and norfloxacin. Conclusions: The study conducted in the Clinical and Bacteriological Laboratory found bacteria with higher frequency in diabetic patients, evaluating sensitivity and resistance through urine cultures and antibiograms, relating the pathogenic germ with resistance which helps in facilitating the selection of more effective antibiotics.
Introducción: Las infecciones de tracto urinario (ITU), en pacientes diabéticos pueden ocasionar complicaciones graves como la bacteriemia. Los principales factores de riesgo asociados se encuentran: poliuria, cistitis, disuria y pielonefritis, condiciones que contribuyen a una mayor incidencia en esta población. El trabajo presento como objetivo determinar las bacterias con mayor frecuencia en pacientes con Diabetes Mellitus Tipo II (DM II) que presentaron ITU, mediante el análisis de historias clínicas y base de datos para la medición de la sensibilidad y resistencia microbiana. Se realizó un estudio descriptivo y transversal, se revisó historias clínicas y bases de datos con pacientes DM II que asistieron a un laboratorio privado. La información recopilada incluyó datos microbiológicos relacionados con ITU. Los datos obtenidos fueron procesados y analizados estadísticamente, utilizando porcentajes para describir la distribución de microorganismo, perfiles de sensibilidad y resistencia antimicrobiana. Resultados: Los microorganismos identificados, Escherichia coli, el patógeno más frecuente, representando el 37.5% de los aislamientos, seguido Staphylococcus aureus (23.75%), Streptococcus agalactiae (17.5%) miembros de la familia Enterobacteriaceae (10%). En cuanto la resistencia antimicrobiana, gentamicina mostró niveles más altos de resistencia, alcanzando un 89.33%. Por otro lado, los antibióticos con mayor frecuencia de sensibilidad fueron amikacina, ciprofloxacino y norfloxacino. Conclusiones: El estudio realizado en el Laboratorio Clínico y Bacteriológico se encontró bacterias con mayor frecuencia en pacientes diabéticos, evaluando la sensibilidad y resistencia mediante urocultivos y antibiogramas, relacionando el germen patógeno con la resistencia que ayuda en facilitar la selección de antibióticos más eficaz.
Keywords: DIABETES; SENSIBILIDAD; RESISTENCIA; ANTIBIÓTICOS Y BACTERIAS